2018
DOI: 10.1038/s41598-018-23935-w
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Closure of Left Atrial Appendage significantly affects Lipidome Metabolism

Abstract: Patients with non-valvular atrial fibrillation (AF) and a high risk for oral anticoagulation can be treated by percutaneous implantation of left atrial appendage occlusion devices (LAAC) to reduce the risk of cardio-embolic stroke. This study evaluates whether LAAC may influence lipid metabolism, which has never been investigated before. Patients with successful LAAC were included consecutively. Venous peripheral blood samples of patients were collected immediately before (T0, baseline) and 6 months after (T1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…raised end-diastolic pressures, hinting at altered diastolic and sustained systolic ventricular function. 40 In these atrial-fibrillation patients and in our patients, values for PL with fatty acids of higher carbon numbers were altered. However, whilst in the atrial-fibrillation patients analyte concentrations were higher than in controls, we found lower analyte concentrations in patients than in controls.…”
Section: Altered Cell Signalling and Metabolism As Indicators Of Subtmentioning
confidence: 50%
See 1 more Smart Citation
“…raised end-diastolic pressures, hinting at altered diastolic and sustained systolic ventricular function. 40 In these atrial-fibrillation patients and in our patients, values for PL with fatty acids of higher carbon numbers were altered. However, whilst in the atrial-fibrillation patients analyte concentrations were higher than in controls, we found lower analyte concentrations in patients than in controls.…”
Section: Altered Cell Signalling and Metabolism As Indicators Of Subtmentioning
confidence: 50%
“…39 Findings in atrial-fibrillation patients with a biventricular system, in whom blood PL levels rose between closure of left atrial appendage (LAA) and 6 months thereafter, support the assumption that decreased PL levels in our patients indicate subtle stages of HF with slightly raised end-diastolic pressures, hinting at altered diastolic and sustained systolic ventricular function. 40 In these atrial-fibrillation patients and in our patients, values for PL with fatty acids of higher carbon numbers were altered. However, whilst in the atrial-fibrillation patients analyte concentrations were higher than in controls, we found lower analyte concentrations in patients than in controls.…”
Section: Altered Cell Signalling and Metabolism As Indicators Of Subtmentioning
confidence: 50%
“…16 In a recent publication, rehospitalizations for heart failure were reported in 17% of the patients after interventional LAA closure; however, the development of heart failure was attributed to pre-existing cardiac disease in this study. 22,23 At present, the clinical relevance of this phenomenon during long-term follow-up is unknown. 18,19 Progressive left atrial enlargement is a well-known phenomenon in permanent nAF and has also been documented after interventional LAA closure.…”
Section: Discussionmentioning
confidence: 99%
“…Further potentially disastrous consequences in our patient were a right atrial appendage thrombus and bidirectional interatrial shunting through a Apart from haemodynamic and endocrine consequences, LAA closure has been shown to affect glycolysis, tricarboxylic acid, urea, and lipidome metabolism. 22,23 At present, the clinical relevance of this phenomenon during long-term follow-up is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the future of percutaneous LAA occlusion will depend on complications and on the long-term efficacy in stroke prevention. It will likely take decades to see if suggestions of altered lipidomes 47 have any significant clinical impact. On the other hand, persistent peridevice leak and device thrombosis do occur, 48 and there is likely room for improvement in post–LAA occlusion regimens for anticoagulation/antiplatelet therapy.…”
Section: The Futurementioning
confidence: 99%